Sentinel-2 time series analysis for monitoring multi-taxon biodiversity in mountain beech forests - Parisi, Francesco; Vangi, Elia; Francini, Saverio; D’Amico, Giovanni; Chirici, Gherardo; Marchetti, Marco; Lombardi, Fabio; Travaglini, Davide; Ravera, Sonia; De Santis, Elena; Tognetti, Roberto (Frontiers in Forests and Global Change, 2023)
Biodiversity monitoring represents a major challenge to support forest ecosystem management and to support conservation of those strategies that have shifted from single-species protection to multi-taxon approaches. Although in-situ campaigns are the most accurate way of measuring certain aspects of biodiversity, they are expensive, time demanding, and sometimes impossible. In this context, remote sensing is a powerful tool, continuously providing free data at a different range of spatial and temporal scales, consistent, and with a high degree of homogeneity. In particular, the freely available Sentinel-2 (S2) mission - with 10 m spatial resolution and five days of revisitation time all over the world - has great potential to produce reliable proxies for biological diversity. In the Gran Sasso e Monti della Laga, (GSML) and Cilento Vallo di Diano e Alburni (CVDA) National Parks, we surveyed living trees, deadwood, and Tree-related Microhabitats (TreMs). Yet, we sampled the beetle fauna, breeding birds, and epiphytic lichens. First, we calculated the Shannon’s entropy, the Simpson’s diversity, and Margalef's richness indices, which provide quantitative information on different aspects of biodiversity. Then, to produce variables for biodiversity assessment, we exploited S2 data acquired in the four years, 2017-2021. S2 images were used to construct time series spectral bands and photosynthetic indices, from which 91 harmonic metrics were derived. For each taxon and multi-taxon community, relationships between S2 metrics, biodiversity indices, and forest structural variables were investigated. Overall, 241 beetle, 27 bird, and 59 lichen species were recorded. The diversity indices were higher for the multi-taxon community than for the single taxa and were generally higher in the CVDA site than in GSML, except for the bird community. The highest values of the median absolute Pearson correlation were recorded for multi-taxon and beetle communities (0.52 and 0.38, respectively) in CVDA, and for lichen and beetle communities (0.34 and 0.26 respectively) in GSML. Our results demonstrate that S2 data can be used for identifying potential biodiversity hotspots, showing that the herein presented harmonic metrics are informative for several taxa inhabiting wood, giving concrete support to cost-effective biodiversity monitoring and nature-based forest management in complex mountain systems.